2011
DOI: 10.1021/la203357p
|View full text |Cite
|
Sign up to set email alerts
|

On the Crucial Importance of the pH for the Formation and Self-Stabilization of Protein Microgels and Strands

Abstract: Stable suspensions of protein microgels are formed by heating salt-free β-lactoglobulin solutions at concentrations up to about C = 50 g·L(-1) if the pH is set within a narrow range between 5.75 and 6.1. The internal protein concentration of these spherical particles is about 150 g·L(-1) and the average hydrodynamic radius decreases with increasing pH from 200 to 75 nm. The formation of the microgels leads to an increase of the pH, which is a necessary condition to obtain stable suspensions. The spontaneous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 18 publications
11
52
0
Order By: Relevance
“…It is likely that this effect of the protein concentration is caused by the concentration dependence of the pK a of the proteins in salt free solutions. The proteins that did not form microgels aggregated mainly into strands, but in addition a small amount of denatured proteins and small oligomers was formed, confirming the earlier results by Donato et al [14] The formation of microgels and strands, as a function of time during heating was studied in more detail at C = 40 g/L and pH 5.8 [15]. It was found that microgels were formed already very early on during the reaction, when less than one percent of the proteins had denatured and aggregated.…”
Section: Effect Of the Phsupporting
confidence: 86%
See 3 more Smart Citations
“…It is likely that this effect of the protein concentration is caused by the concentration dependence of the pK a of the proteins in salt free solutions. The proteins that did not form microgels aggregated mainly into strands, but in addition a small amount of denatured proteins and small oligomers was formed, confirming the earlier results by Donato et al [14] The formation of microgels and strands, as a function of time during heating was studied in more detail at C = 40 g/L and pH 5.8 [15]. It was found that microgels were formed already very early on during the reaction, when less than one percent of the proteins had denatured and aggregated.…”
Section: Effect Of the Phsupporting
confidence: 86%
“…The average R h of the microgels was found to increase with decreasing pH from about 70 nm at pH 6.0 to about 130 nm at pH 5.75, but their protein density calculated as = M/[(4/3) R h 3 ·N a ] did not depend significantly on the pH and was found to be 0.15 ± 0.5 g/mL. In this pH-range the size of the microgels did not depend on the protein concentration between 10 and 50 g/L, A similar increase of R h with decreasing pH was reported Adapted from Phan-Xuan et al [15,18]. recently for ␤-lg microgels formed at a C = 2.5 g/L by Murphy et al [16].…”
Section: Effect Of the Phsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the mechanism of protein unfolding, aggregation, and gelation is rather complex. Gelation depends not only on pH and ionic strength but also on other conditions prevailing in the aqueous solution (i.e., ionic calcium content, fat content, presence of lactose, and protein composition/concentration) and heating treatments (Dalgleish and Banks 1991;Law and Leaver 2000;Nicorescu et al 2008;Tuan et al 2011;Verheul et al 1998;Anema and Li 2003). For instance, it was shown that the type of heating method (direct or indirect) used for protein denaturation should not be overlooked.…”
Section: Introductionmentioning
confidence: 99%